Challenges of Utilizing E-Learning Systems in Public Universities in Jordan - Al-Shboul, Muhannad Anwar; Alsmadi, Izzat (International Journal of Emerging Technologies in Learning (iJET), 2010)
This research paper lists and discusses major challenges and barriers that may face faculty members at the public universities in Jordan in employing e-Learning systems authoring tools in their instructions. It also proposes several suggestions for the administrators in public universities in Jordan for what they could do to improve the utilization of e-Learning authoring tools at their campuses. E-Learning systems authoring tools allow instructors to easily create and deliver their e-contents and e-lectures. Furthermore, online course materials which uploaded by using such authoring tools could be viewed by any popular web browser system.